2021
DOI: 10.1002/cam4.4322
|View full text |Cite
|
Sign up to set email alerts
|

Trust and shared decision‐making among individuals with multiple myeloma: A qualitative study

Abstract: Background Multiple myeloma (MM) is an incurable cancer with complex treatment options. Trusting patient–clinician relationships are essential to promote effective shared decision‐making that aligns best clinical practices with patient values and preferences. This study sought to shed light on the development of trust between MM patients and clinicians. Methods Nineteen individual semi‐structured interviews were conducted with MM patients within 2 years of initial diagnosis or relapse for this qualitative stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Most families in the study had positive attitudes and experiences with their GPs, including the ability to trust, have open and honest conversations, and being made aware of important information regarding their child’s health, which would all lead to greater awareness and confidence, and thereby improving their overall healthcare experience and well-being. This was indeed affirmed by several previous studies, which had shown that building trust and rapport in doctor–patient relationships through open communication, patient engagement and shared decision-making mitigates patients’ feelings of anxiety and vulnerability, thus improving their overall healthcare experience 33 34…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Most families in the study had positive attitudes and experiences with their GPs, including the ability to trust, have open and honest conversations, and being made aware of important information regarding their child’s health, which would all lead to greater awareness and confidence, and thereby improving their overall healthcare experience and well-being. This was indeed affirmed by several previous studies, which had shown that building trust and rapport in doctor–patient relationships through open communication, patient engagement and shared decision-making mitigates patients’ feelings of anxiety and vulnerability, thus improving their overall healthcare experience 33 34…”
Section: Discussionmentioning
confidence: 54%
“…This was indeed affirmed by several previous studies, which had shown that building trust and rapport in doctor–patient relationships through open communication, patient engagement and shared decision-making mitigates patients’ feelings of anxiety and vulnerability, thus improving their overall healthcare experience. 33 34 …”
Section: Discussionmentioning
confidence: 99%
“…47,48 Trust can be built through empathetic, active listening by the physician, encouraging questions, providing detailed explanations of imaging and laboratory results, avoiding judgmental behaviors, and seeking to understand the patient's goals and expectations for treatment. [47][48][49] Additionally, incongruency between first and second opinions was identified to impact patient trust in their physicians; however, further research is required to better understand this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the trust and support patients had in their physicians, they were able to engage in discussions of future focused treatment of MM, though they had preferences to not follow guidelines at the present time. The long-term and incurable nature of MM have an influence on the perspective on and the decisions surrounding standards of care [ 26 ]. There is an understanding of and anticipation of the treatment process being long itself and being lifelong, and intentionally not following guidelines at present provides patients and physicians with choices in the future.…”
Section: Discussionmentioning
confidence: 99%